Theory of biopolymer templating mechanisms - Phan, Tam Thi Minh (Kansas State University, 2021)
Biopolymer templating is the process in which two or more flexible biopolymers identify specific zipper-like binding state encoded by the sequence of sidechains. The challenge in studying biopolymer templating is that experiments only give macroscopic results from which microscopic processes must be inferred. Here we build a theory of biopolymer templating mechanisms via interactions of the polymers in mis-aligned and aligned states using a random walk model to understand the thermodynamics and kinetics of various biomolecules. We consider two types of biopolymer templating, protein aggregation and DNA hybridization. Protein aggregation is associated with numerous neurodegenerative diseases such as Huntington’s and Alzheimer’s while DNA hybridization plays important roles in many fields including nanotechnology, biotechnology. Surprisingly, we find that although protein and DNA systems share many similarities, they have different results: the mis-aligned states slow down and hinder the protein aggregation while nonspecific binding helps DNA to perform the alignment search during hybridization, which accelerates the hybridization rate. The findings can contribute to a better understanding of the nature of biopolymer templating in many systems.
Keywords: Bioplymer templating; DNA hybridization; Protein aggregation